Developing Creative Expression through Drawing in Visual Arts Education - Rustamov Axtam Muxtorovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines the role of drawing in fostering creative expression among students in visual arts education. It explores how structured drawing activities enhance technical skills, creative thinking, and cultural awareness. The study emphasizes the integration of traditional motifs and national values to support students’ artistic growth and appreciation of cultural heritage.